The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/dmrr.391
|View full text |Cite
|
Sign up to set email alerts
|

The appearance of aggregated erythrocytes in the peripheral blood of individuals with insulin resistance

Abstract: Insulin resistance is associated with an enhanced degree of erythrocyte adhesiveness/aggregation and this is related to the presence of enhanced inflammation-sensitive plasma proteins that are part of the acute-phase response. These findings might have hemorheological consequences and might contribute to the pathophysiology of the insulin-resistance syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…However, we disagree about the standardization issue. In fact, we have by now analyzed approximately 2000 samples from different inflammatory conditions and found that the results of the slide test are generally not inferior to those obtained by other commonly used markers of the acute-phase response [9][10][11][12][13][14][15]. We do agree, however, that our slide test is not affected to a significant degree by protein-independent aggregability.The slide test was developed as a low-cost real-time and point of care methodology to reveal the presence of enhanced red cell adhesiveness / aggregation in the peripheral blood [16].…”
supporting
confidence: 65%
“…However, we disagree about the standardization issue. In fact, we have by now analyzed approximately 2000 samples from different inflammatory conditions and found that the results of the slide test are generally not inferior to those obtained by other commonly used markers of the acute-phase response [9][10][11][12][13][14][15]. We do agree, however, that our slide test is not affected to a significant degree by protein-independent aggregability.The slide test was developed as a low-cost real-time and point of care methodology to reveal the presence of enhanced red cell adhesiveness / aggregation in the peripheral blood [16].…”
supporting
confidence: 65%
“…For example, enhanced erythrocyte aggregation has been described in hypertension [38,39], hypercholesterolemia [40,41], hypertriglyceridemia [42], obesity [43] as well as in insulin resistance [5]. Thus, the aggregability of the cells might indeed reflect the presence of lowgrade inflammation and enhanced synthesis of adhesive proteins [44].…”
Section: Discussionmentioning
confidence: 97%
“…The aggregation of red blood cells in the peripheral blood was performed by the ERYTHROSENSE technology [5,18,19]. In brief, blood from the antecubital vein was obtained between 8 and 11 AM following an overnight fast.…”
Section: The Erythrosense Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Erythrocyte deformability and/or aggregation is an important determinant of passage of blood through capillaries. The degree of erythrocyte aggregation is correlated with the IR index HOMA [ 189 , 405 ]. High hematocrit is inversely related to small vessel endothelial‐dependent vasodilatation [ 280 ].…”
Section: Microcirculation and The Metabolic Syndromementioning
confidence: 99%